1794 Does Site of Pulse Oximeter Probe Placement Affect Observed Saturation Values in Babies with PDA or Respiratory Support?. (October 2012) - Suresh, P; Cheadle, W; Gupta, S
Abstract : Background: Pulse oximetry is routinely utilised for monitoring oxygen saturations in newborn babies. The site for pulse oximeter probe placement is randomly selected and saturations targeted according to the unit policy. Aim: To study whether site of pulse oximeter probe placement would affect observed saturation values in preterm babies on respiratory support and or having patent ductus arteriosus (PDA)? Methods: Babies born < 32 weeks gestation and admitted to the tertiary level neonatal unit were randomly included in this prospective pilot study. They were allocated to one of 4 groups (Figure 1 ). One probe was placed on right upper limb (pre-ductal) and other on lower limb (post-ductal). Simultaneous continuous saturation recording was done for at least 6 hours using Radical-7, Masimo® pulse oximeters that recorded data every 2 seconds. At the end of the recording period data was downloaded using the software and analysed using SPSS® version 19. Results: Twenty babies were enrolled in this study and 500, 000 data points recorded. The mean pre-ductal saturations were lower than post-ductal saturations in all groups except the group not having a PDA and not on respiratory support (figure 1 ). Conclusions: The site of measurement can affect the observed oxygen saturation values and hence should be taken in account while bedside monitoring and planning clinical trials.